EVALUATING THE ROLE OF RESPONSIBILITY ACCOUNTING IN ENHANCING COST CONTROL AND MANAGERIAL ACCOUNTABILITY: EVIDENCE FROM PT INDOFOOD SUKSES MAKMUR TBK - Nanda Putri Najwa Nanda; Apriliyani; Ninuk Riesmiyantiningtias (Universitas Tulungagung, 2025)
Increasing competition in the manufacturing industry has intensified the need for effective production cost control to maintain operational efficiency and organizational competitiveness. Although responsibility accounting has been widely recognized as a managerial control system, empirical evidence regarding its effectiveness in enhancing cost control and managerial accountability within Indonesian manufacturing companies remains limited. This study aims to evaluate the role of responsibility accounting in enhancing cost control and managerial accountability at PT Indofood Sukses Makmur Tbk. A qualitative descriptive research design was employed using secondary data obtained from the company's published annual reports, audited financial statements, and other relevant corporate publications covering the 2021–2023 period. Data were analyzed through documentary analysis and budget variance analysis by comparing budgeted and actual production costs, including direct materials, direct labor, and manufacturing overhead. The findings indicate that responsibility accounting provides an effective framework for monitoring production costs through clearly defined responsibility centers, systematic budgeting, and performance reporting. Budget variance analysis enables management to identify favorable and unfavorable cost deviations, evaluate managerial performance objectively, and implement timely corrective actions. The study further reveals that responsibility accounting strengthens managerial accountability by improving budget discipline, operational efficiency, and evidence-based decision-making. These findings contribute to the management accounting literature by providing empirical evidence on the strategic role of responsibility accounting in supporting cost control and organizational governance. Practically, the study highlights the importance of integrating responsibility accounting with continuous performance evaluation to improve resource utilization and enhance managerial effectiveness in manufacturing organizations.